Effects of alpha particles on the CTEM driven zonal flow in deuterium–tritium tokamak plasmas. (1st May 2022) - Hussain, M. S.; Guo, Weixin; Wang, Lu
Abstract: The effects of fusion-born alpha ( α ) particles on zonal flow (ZF) driven by collisionless trapped electron mode (CTEM) turbulence are analytically investigated, using gyrokinetic and bounce kinetic theories in the deuterium–tritium (D–T) tokamak plasmas. It is found that ZF growth rate is increased by α particles because of the reduction of polarization shielding as well as enhancement of CTEM instability. The results of this paper are qualitatively consistent with the enhancement of the level of residual ZF by α particles in (Cho and Hahm 2019 Nucl. Fusion 59 066026). The parametric dependence of ZF growth rate is also analyzed. The increment of ZF growth rate is further enhanced by α particles with higher fraction and steeper density profile. Besides, the dependence of ZF growth rate on electron temperature T e could be changed qualitatively by the presence of α particles when T i = T e . Moreover, the difference of ZF growth rates in the presence of α particles with slowing down and equivalent Maxwellian distribution functions is very weak. These results could be very important for accurate prediction of the confinement in the future burning plasmas such as International Thermonuclear Experimental Reactor and China Fusion Engineering Test Reactor.